The complexity of patient safety in the Intensive Care Unit (Research, Society and Development, 2020)
Issues associated with patient safety are a health problem worldwide and have been widely discussed at the most diverse levels of health care. Objective: to analyze the meaning of conditions for patient safety in the intensive care unit from the nurses' perspective. Methodology: a qualitative study using the Straussian Grounded theory, approved by the Research Ethics Committee. With 20 nursing participants from two state public hospitals in Rondônia, from a semi-structured interview, between August 2018 and September 2019, analyzing the data according to the method, considering: open, axial and integration coding. Results: three categories were obtained from the analysis: “The work environment is at high risk of harm”; Recognizing human resources as determinants for active failures; and Experiencing disorganized work processes. The following phenomenon emerged from these categories: Considering the structure, professionals and work processes that are challenging for patient safety. Conclusion: Each category and subcategories represent the conditions experienced by nurses that directly influence the safety of critical patients in the intensive care unit. The results provide subsidies for mitigating actions or even resolving these conditions, strengthening the actions of nursing and the multidisciplinary team and, therefore, patient safety in the intensive care unit.